2016
DOI: 10.1128/aem.00462-16
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Sweetness of Yoghurt through Metabolic Remodeling of Carbohydrate Metabolism in Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus

Abstract: Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus are used in the fermentation of milk to produce yoghurt. These species normally metabolize only the glucose moiety of lactose, secreting galactose and producing lactic acid as the main metabolic end product. We used multiple serial selection steps to isolate spontaneous mutants of industrial strains of S. thermophilus and L. delbrueckii subsp. bulgaricus that secreted glucose rather than galactose when utilizing lactose as a carbon sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
1
41
0
3
Order By: Relevance
“…The gal promoter plays an important role in the galactose phenotype of S. thermophilus [42,50,51,52,53,54]. It has been found that the point mutations in the promoter region of gal operon lead to low expression level of the Leloir pathway enzymes for galactose utilization [42,50].…”
Section: Technological and Functional Properties Of S Thermophilusmentioning
confidence: 99%
See 2 more Smart Citations
“…The gal promoter plays an important role in the galactose phenotype of S. thermophilus [42,50,51,52,53,54]. It has been found that the point mutations in the promoter region of gal operon lead to low expression level of the Leloir pathway enzymes for galactose utilization [42,50].…”
Section: Technological and Functional Properties Of S Thermophilusmentioning
confidence: 99%
“…Recently, it was found that spontaneous galactose-fermenting mutant St1-Ga + -1 has the same mutation in the −10 region of galK , i.e., TACAAT, which is closer to the consensus sequence TATAAT. Strain St1-Ga + -1 can ferment galactose, while its mother strain St1-WT is unable to utilize galactose, although it has intact galKTEM genes [54]. At the same time, Sørensen et al found that another spontaneous galactose-fermenting mutant St2-Ga + -1 had a C-to-A mutation between the −10 region and the galK transcription initiation site [54].…”
Section: Technological and Functional Properties Of S Thermophilusmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered by nutritionists to have a high nutritional value and positive bioactive effects. To satisfy consumer demands, a number of additional ingredients may be added to yogurt, including natural or artificial colors, sucrose or artificial sweeteners, texturizing agents (Sørensen et al, 2016), prebiotic ingredients and probiotic bacteria (Oliveira et al, 2015). In recent years, some vegetable (Kiros et al, 2016) and fruit preparations (Oliveira et al, 2015) along with plants extracts (Balthazar et Taraxacum officinale, known as the dandelion, is a member of the Asteraceae/Compositae family.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using WGS as a means to uncovering new pathways for flavor generation, the technology can also be used as a screening tool to monitor changes in known pathways in the generation of spontaneous mutants with enhanced flavor capabilities. This approach was taken by Sørensen et al (2016) in an elegant study where WGS analysis of spontaneous mutants derived from strains of S. thermophilus and Lb. delbrueckii ssp.…”
Section: Streptococcus Thermophilusmentioning
confidence: 99%